Revealing oxidative damage to enzymes of carbohydrate metabolism in yeast: An integration of 2D DIGE, quantitative proteomics, and bioinformatics - Boone, Cory H. T.; Grove, Ryan A.; Adamcova, Dana; Braga, Camila P. [UNESP]; Adamec, Jiri (Wiley-Blackwell, 2016)
Clinical usage of lidocaine, a pro-oxidant has been linked with severe, mostly neurological complications. The mechanism(s) causing these complications is independent of the blockade of voltage-gated sodium channels. The budding yeast Saccharomyces cerevisiae lacks voltage-gated sodium channels, thus provides an ideal system to investigate lidocaine-induced protein and pathway alterations. Whole-proteome alterations leading to these complications have not been identified. To address this, S. cerevisiae was grown to stationary phase and exposed to an LC50 dose of lidocaine. The differential proteomes of lidocaine treatment and control were resolved 6 h post exposure using 2D DIGE. Amine reactive dyes and carbonyl reactive dyes were used to assess protein abundance and protein oxidation, respectively. Quantitative analysis of these dyes (>= 1.5-fold alteration, p <= 0.05) revealed a total of 33 proteoforms identified by MS differing in abundance and/or oxidation upon lidocaine exposure. Network analysis showed enrichment of apoptotic proteins and cell wall maintenance proteins, while the abundance of proteins central to carbohydrate metabolism, such as triosephosphate isomerase and glyceraldehyde-3-phosphate dehydrogenase, and redox proteins superoxide dismutase and peroxiredoxin were significantly decreased. Enzymes of carbohydrate metabolism, such as phosphoglycerate kinase and enolase, the TCA cycle enzyme aconitase, and multiple ATP synthase subunits were found to be oxidatively modified. Also, the activity of aconitase was found to be decreased. Overall, these data suggest that toxic doses of lidocaine induce significant disruption of glycolytic pathways, energy production, and redox balance, potentially leading to cell malfunction and death.
Keywords: 2D DIGE; Carbohydrate metabolism; Cell biology; Lidocaine toxicity; Proteomics; Systems biology